PEMBELAJARAN FIKIH KONTEKSTUAL DI PONDOK PESANTREN TAHFIZ DAARUL QUR’AN ISTIQOMAH - Ilmi, Zainal; Nur Aini, Syarifah (CV. Lafadz Jaya, 2024)
Fiqh, as an Islamic religious education closely related to social contexts, is often taught merely as a transfer of knowledge without practical implementation. This results in students struggling to connect their studies with real life, as academic concepts they receive are abstract. Hence, contextual Fiqh learning is necessary. This study aims to explore (1) the overview of contextual Fiqh learning and (2) the concept of contextual Fiqh learning at Pondok Pesantren Tahfizh DQI. This research is a field study with a qualitative approach. The results show four characteristics of contextual learning: activating existing knowledge, applying knowledge and experience, acquiring new knowledge deductively, and learning in an enjoyable environment. The concept of contextual Fiqh learning involves planning based on the study of the text being taught and linking it with the surrounding environment. Implementation includes knowledge construction, inquiry process, modeling, and questioning. Evaluation is conducted formatively and summatively through oral tests, written tests, and performance assessments, but only covers cognitive and psychomotor aspects.